Teachers with autonomy-supportive teaching behaviour in honours education - Ron Weerheijm; Eva Voncken (Journal of the European Honors Council, 2025)
In excellence and honours education in the Netherlands within secondary vocational education (MBO), higher vocational education (HBO) and higher education (WO), stimulating students' autonomy development is an important goal. An autonomy-supportive teaching style forms an essential part of a teacher’s pedagogical-didactic actions. Literature research reveals that an autonomy-supportive teaching style is still mostly described in terms of broad constructs, based on the student perspective, being open to the student, actively supporting motivation development and supporting self-regulation. However, little has yet been described about the concrete pedagogical-didactic actions of teachers and what kinds of learning environments are facilitative in terms of autonomy support on these four constructs. Using 21 semi-structured interviews with teachers in MBO, HBO and WO, this paper offers concrete insights on the above constructs across three broad themes: the design of the learning environment and facilitation of the teacher, the interpersonal student-teacher relationship, teacher interventions and learning activities both for the group as a whole and individually. The interviews generated a series of concrete autonomy-supportive interventions, such as providing space for student curiosity and teaching students to formulate their own learning goals. This provides teachers with a starting point to design their own teaching and concrete pedagogical-didactic actions to shape autonomy development in their teaching practice.